2016
DOI: 10.1186/s13063-016-1740-3
|View full text |Cite
|
Sign up to set email alerts
|

Using a smartphone app to reduce cognitive vulnerability and mild depressive symptoms: Study protocol of an exploratory randomized controlled trial

Abstract: BackgroundDepression is a major challenge worldwide, with significant increasing personal, economic, and societal costs. Although empirically supported treatments have been developed, they are not always available for patients in routine clinical care. Therefore, we need effective and widely accessible strategies to prevent the onset of the very first depressive symptoms. Mental health apps could prove a valuable solution for this desideratum. Although preliminary research has indicated that such apps can be u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…The following measures have been adapted into Romanian and successfully used in two previous trials testing another version of the app, and they have shown adequate psychometric properties [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The following measures have been adapted into Romanian and successfully used in two previous trials testing another version of the app, and they have shown adequate psychometric properties [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…Information on the development of the application and its clinical relevance has been presented at several international and national conferences. A first exploratory study protocol on the efficacy of the app in reducing cognitive vulnerability and mild depressive symptoms has already been published [ 36 ]. More information regarding research progress and dissemination can be found at the project’s designated website [ 60 ].…”
Section: Methodsmentioning
confidence: 99%
“…18 Currently, several trials are ongoing to investigate gamification as an intervention tool in different domains of mental health and mental healthcare. 19…”
Section: Introductionmentioning
confidence: 99%
“…18 Currently, several trials are ongoing to investigate gamification as an intervention tool in different domains of mental health and mental healthcare. 19 Utilizing digital games in mental health services requires information not only on their effects but also on the perceptions, attitudes and experiences of both service users and professionals regarding games and gaming. However, research on these topics is currently scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Exploiting larger screen resolutions and multimedia capabilities, one finds examples of multimodal learning materials using both audio and video guides [133,167], using pictures [83, 86-88, 117, 129], audio [83,87,88,117], music [86][87][88] and video [83,88,156]. Leveraging the improved connectivity and ubiquity of smartphones, some authors offer access to entire online libraries of learning materials [127,167]; others utilize in-app prompting as intervention techniques, e.g., sending reminders to use the app [87,103,104,118,159], motivational messages [70] or messages from the therapist [90,163]. Exploiting the improved interactivity of smartphones, we find interactive quizzes for training skills and improved learning [78,127], assessments for panic attacks [144], suicidal intentions [122], symptoms Chapter 2.…”
Section: Coverage Of Technical Dimensionsmentioning
confidence: 99%